Dasar Hukum dan Prinsip Perbankan Syariah di Indonesia - Sari, Adelia; Aulianisa, Izza; Ilham (STEI Kanjeng Sepuh Gresik Jawa Timur, 2025)
This article discusses the legal basis and operational principles of Islamic banking in Indonesia as part of the national financial system based on Islamic teachings. The main objective of Islamic banking is to provide financial services that are fair, transparent, and free from riba, gharar, and maysir practices. This study uses a normative legal approach with a qualitative descriptive method, which examines various laws and regulations and fatwas from the National Sharia Council of the Indonesian Ulema Council (DSN-MUI) as the main sources. The results of the study indicate that Islamic banking is based on two main pillars: Islamic law (Al-Qur'an, Hadith, ijma, qiyas) and positive law as stated in Law No. 21 of 2008. In practice, various principles such as mudharabah, musyarakah, murabahah, ijarah, and qardh are applied to banking products to ensure their compliance with sharia. Despite having a strong legal basis, the implementation of sharia principles in the field still faces several challenges, such as limited regulations, limited public understanding, and operational consistency. Therefore, the role of DSN-MUI is very important in providing legitimacy and guidance in the implementation of sharia principles in the banking sector. This article is expected to provide deeper insight into the regulatory and practical aspects of sharia banking in Indonesia.